Underwater archaeological survey of Dubrovnik-Neretva County (In situ, 2025)
The work on the Croatian Science Foundation's project Undersea Neolithic sites in the Croatian Adriatic includes a special survey of the seabed of coastal counties. A survey of Dubrovnik-Neretva County was planned for 2024. Potential locations were surveyed and archaeological remains were identified that can be roughly dated to the Neolithic period.
Keywords: underwater archaeological survey; Neolithic; Dubrovnik-Neretva County